Hazard-consistent fragility analysis of equipment in NPP structures considering multiple hazard levels - Heekun Ju; Hyung-Jo Jung (Nuclear Engineering and Technology, 2025)
This study investigates the fragility of equipment in nonlinear nuclear structures using hazard-consistent ground motions derived from the Generalized Conditional Intensity Measure (GCIM) approach. Unlike conventional spectra such as the Uniform Hazard Spectrum (UHS), which aggregate intensity measures without considering the seismic scenarios from which they originate, the GCIM method reflects site-specific hazard characteristics by conditioning on rupture scenarios obtained through probabilistic seismic hazard analysis deaggregation. By evaluating multiple levels of ground motion intensity, this study captures how the relative contributions of earthquake magnitude and distance evolve across hazard levels, resulting in changes in the shape and correlation of ground motion parameters. This differences are especially important for nonlinear systems, where in-structure response spectra (ISRS) may shift in frequency and amplitude due to nonlinear behavior, amplifying the effects of input ground motion variability. The results show that GCIM-based ground motions tend to produce lower median fragility estimates compared to those derived from UHS or RG 1.60, while also exhibiting greater dispersion due to explicit scenario-dependent variability. These findings suggest that, especially for equipment housed in nonlinear structures, fragility assessment should account for both structural nonlinearity and hazard-level-dependent ground motion variability.